Preparation and Characterization of Tapioca Starch/Polycaprolactone/Clay Composites - Then, Yoon Yee (2011)
In this work, plasticized tapioca starches (PTSs), blends of PTS and polycaprolactone (PCL), and composites of PTS/clay and PCL/PTS/clay were prepared by melt blending. Both natural clay (MMT) and octadecylamine modified clay (OMMT) were used in this study. OMMT was prepared by cation exchange reaction of Na+ cation in the interlayer of MMT with octadecylammonium cation from octadecylammonium chloride. X-ray diffraction (XRD) results showed that the OMMT has bigger d-spacing than that of original MMT indicating octadecylammonium cation has successfully intercalated into the clay interlayer. Thermogravimetric analysis (TGA), Fourier transform infrared (FTIR) spectroscopy, and elemental analysis also indicated the presence of octadecylammonium cation in the OMMT. PTSs were prepared by gelatinizing and plasticizing tapioca starch with water and glycerol, respectively in a Thermo Haake Polydrive internal mixer. Scanning electron micrographs showed that the tapioca starch formed a continuous phase after it was gelatinized and plasticized with water and glycerol. The study indicated that the tensile, thermal and water absorption properties of PTSs were strongly influenced by the contents of water and glycerol. The PTSs were water sensitive and exhibited low tensile properties. The formulation of tapioca starch, glycerol and water in the weight ratio of 5:1:4 was selected to study the effect of MMT, OMMT or PCL addition on its properties. The composites of PTS/clay were prepared by melt blending of PTS with various amount of MMT or OMMT also in a Thermo Haake Polydrive internal mixer. The XRD and TEM results showed that the composites produced are of intercalated types. Transmission electron micrographs revealed that MMT was better dispersed than that of OMMT in the PTS matrix due to the strong polar interaction between the hydrophilic MMT and PTS. Consequently, higher tensile strength, modulus, thermal stability and storage modulus were observed in PTS/MMT composites compared to those of PTS/OMMT composites as well as neat PTS. However the water resistance property of PTS was improved by the presence of OMMT. The blends of PCL and PTS were prepared by melt blending of PCL and PTS of different compositions also in a Thermo Haake Polydrive internal mixer. The presence of PCL improved the tensile strength, elongation at break, thermal stability and water resistance property of PTS. PCL/PTS/clay composites were also prepared by melt blending the blend and clays. XRD results showed that the composites produced are of intercalated types. Transmission electron micrographs revealed that OMMT was better dispersed than that of MMT in the matrix. Significant improvements in tensile strength (> 60%) and elongation at break (> 1000%) were observed by the addition of 1 php of OMMT. Improvement in water resistance property was also observed in PCL/PTS/OMMT composites. In contrast, no obvious properties improvements were observed for PCL/PTS/MMT composites.